The impact of students' part-time work on educational outcomes - Magdalena Rokicka (University of Essex, Institute for Social and Economic Research (ISER), 2014)
This paper addresses the issue of school students' part-time employment in the last year of compulsory education, and its impact on educational outcomes. Estimating the causal effect is not straightforward. Firstly, those who obtain part-time employment could have certain unobservable characteristics, which also have an impact on their educational outcomes. Secondly, the decisions to work part-time while still in school and to continue education after age 16 might be made simultaneously, which leads to a problem with endogeneity. To account for this, I apply an instrumental approach and a recursive bivariate probit estimation. My results suggest that working part-time during the last year of compulsory education has a negative impact on educational achievements and on participation in education in the subsequent year.
Keywords: 330; students' labour supply; educational attainment; exam results; post-compulsory education participation